Fe/Mg smectite formation under acidic conditions on early Mars. (15th January 2016) - Peretyazhko, T.S.; Sutter, B.; Morris, R.V.; Agresti, D.G.; Le, L.; Ming, D.W.
Abstract: Phyllosilicates of the smectite group detected in Noachian and early Hesperian terrains on Mars have been hypothesized to form under neutral to alkaline conditions. These pH conditions would also be favorable for formation of widespread carbonate deposits which have not been detected on Mars. We propose that smectite deposits on Mars formed under moderately acidic conditions inhibiting carbonate formation. We report here the first synthesis of Fe/Mg smectite in an acidic hydrothermal system [200 °C, pHRT  ∼ 4 (pH measured at room temperature) buffered with acetic acid] from Mars-analogue, glass-rich, basalt simulant with and without aqueous Mg or Fe(II) addition under N2 -purged anoxic and ambient oxic redox conditions. Synthesized Fe/Mg smectite was examined by X-ray-diffraction, Mössbauer spectroscopy, visible and near-infrared reflectance spectroscopy, scanning electron microscopy and electron microprobe to characterize mineralogy, morphology and chemical composition. Alteration of the glass phase of basalt simulant resulted in formation of the Fe/Mg smectite mineral saponite with some mineralogical and chemical properties similar to the properties reported for Fe/Mg smectite on Mars. Our experiments are evidence that neutral to alkaline conditions on early Mars are not necessary for Fe/Mg smectite formation as previously inferred. Phyllosilicate minerals could instead have formed under mildly acidic pH conditions. Volcanic SO2 emanation and sulfuric acid formation is proposed as the major source of acidity for the alteration of basaltic materials and subsequent formation of Fe/Mg smectite.